Examination of policies and MEAs commitment by SIDS for sustainable management of the Caribbean Sea - Singh, Asha (2008)
Reviews the regional responses by the Small Island Developing States (SIDS) and other agencies in dealing with pollution from land and marine-based activities and biodiversity loss through the major legal instruments (MEAs) and policies.